2007
DOI: 10.1212/01.wnl.0000277320.50685.7c
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and Alzheimer disease mortality

Abstract: Background-We previously reported that the Mediterranean diet (MeDi) is related to lower risk for Alzheimer disease (AD). Whether MeDi is associated with subsequent AD course and outcomes has not been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
129
0
10

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(152 citation statements)
references
References 76 publications
(21 reference statements)
13
129
0
10
Order By: Relevance
“…These findings are congruent with data from animal models showing that fat intake may be related not only to vascular risks but also to a direct effect of polyunsaturated fatty acids on Aβ accumulation [134]. Other evidence suggests that the "Mediterranean diet" is associated with a lower risk for AD [135] and a lower mortality once AD is established [136]. One hypothesis to explain this relationship is that the Mediterranean diet reduces vascular risks; however, a recent analysis suggests this is not the case [137].…”
Section: Epidemiologic Studiessupporting
confidence: 83%
“…These findings are congruent with data from animal models showing that fat intake may be related not only to vascular risks but also to a direct effect of polyunsaturated fatty acids on Aβ accumulation [134]. Other evidence suggests that the "Mediterranean diet" is associated with a lower risk for AD [135] and a lower mortality once AD is established [136]. One hypothesis to explain this relationship is that the Mediterranean diet reduces vascular risks; however, a recent analysis suggests this is not the case [137].…”
Section: Epidemiologic Studiessupporting
confidence: 83%
“…For example, application of HFD for APP transgenic mice exacerbated pathological alterations in the brain and their memory deficits (6,7). In contrast, it is widely known that composite dietary patterns such as the Mediterranean diet, characterized by high intake of vegetables, unsaturated fatty acids, and wine, are related to lower risk for AD (8). These studies clearly indicate that there is an association between metabolic conditions and a higher risk of sporadic AD.…”
mentioning
confidence: 99%
“…A study showed that individuals with medium and high adherence to the MeDi lived 1.33 and 3.91 years longer, respectively, than those with low adherence 37 .…”
Section: Evidence Of the Benefits Of The Mediterranean Diet On Cognitmentioning
confidence: 99%
“…However, we also consider that the MeDi, rather than single foods or nutrients, may constitute an effective preventive strategy with low cost, few side effects, and strong epidemiological health outcomes, which may translate to significantly better public health 14,21,37 .…”
Section: O N C L U S I O Nmentioning
confidence: 99%